The transition to Post-industrial BMI values among US children - John Komlos; Ariane Breitfelder; Marco Sunder (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
Background: The trend in the BMI values of US children has not been estimated very convincingly because of the absence of longitudinal data. Our object is to estimate time series of BMI values by birth cohorts instead of measurement years. Methods: We use five regression models to estimate the BMI trends of non-Hispanic US-born black and white children and adolescents ages 2-19 between 1941 and 2004. Results: The increase in BMIZ values during the period considered was 1.3σ (95% CI: 1.16σ; 1.44σ) among black girls, 0.8σ for black boys, 0.7σ for white boys, and 0.6σ for white girls. This translates into an increase in BMI values of some 5.6, 3.3, 2.4, and 1.5 units respectively. While the increase in BMI values started among the birth cohorts of the 1940s among black girls, the rate of increase tended to accelerate among all four ethnic/gender groups born in the mid-1950s – early-1960s. Conclusion: Some regional evidence leads to the conjecture that the spread of automobiles and radios affected the BMI values of boys already in the interwar period. We suppose that the changes in lifestyle associated with the labor saving technological developments of the 20th century are associated with the weight gains observed. The increased popularity of television viewing was most prominently associated with the contemporaneous acceleration in BMI gain.
urn:nbn:de:bvb:19-epub-4304-0
Keywords: I31; 330; BMI; BMIZ; US; children; youth; adolescents; NHANES; obesity epidemic; overweight; Gesundheit; Ernährungsverhalten; Index; Kinder; Jugendliche; Technischer Fortschritt; USA